The last bc the + and - are different that means it will be subtracted.
Answer:
Three times
Step-by-step explanation:
Given
Figures: Rectangular Prism and Rectangular Pyramid
Let the dimension of the prism be:
![l = length](https://tex.z-dn.net/?f=l%20%3D%20length)
![w = width](https://tex.z-dn.net/?f=w%20%3D%20width)
![h = height](https://tex.z-dn.net/?f=h%20%3D%20height)
Amount of sand used is the volume (V1) and it is calculated using;
![V_1 = l * w * h](https://tex.z-dn.net/?f=V_1%20%3D%20l%20%2A%20w%20%2A%20h)
![V_1 = lw h](https://tex.z-dn.net/?f=V_1%20%3D%20lw%20h)
Since the pyramid has the same base area and height as the prism, the its dimension would be:
![l = length](https://tex.z-dn.net/?f=l%20%3D%20length)
![w = width](https://tex.z-dn.net/?f=w%20%3D%20width)
![h = height](https://tex.z-dn.net/?f=h%20%3D%20height)
Amount of sand used is the volume (V2) and it is calculated using;
![V_2 = \frac{1}{3}*(lwh)](https://tex.z-dn.net/?f=V_2%20%3D%20%5Cfrac%7B1%7D%7B3%7D%2A%28lwh%29)
So, we have:
![V_1 = lw h](https://tex.z-dn.net/?f=V_1%20%3D%20lw%20h)
![V_2 = \frac{1}{3}*(lwh)](https://tex.z-dn.net/?f=V_2%20%3D%20%5Cfrac%7B1%7D%7B3%7D%2A%28lwh%29)
Substitute lwh for V1 in the second equation
![V_2 = \frac{1}{3}V_1](https://tex.z-dn.net/?f=V_2%20%3D%20%5Cfrac%7B1%7D%7B3%7DV_1)
Multiply both sides by 3
![3 * V_2 = \frac{1}{3}V_1 * 3](https://tex.z-dn.net/?f=3%20%2A%20V_2%20%3D%20%5Cfrac%7B1%7D%7B3%7DV_1%20%2A%203)
![3 * V_2 = V_1](https://tex.z-dn.net/?f=3%20%2A%20V_2%20%3D%20V_1)
Reorder
![V_1 = 3 * V_2](https://tex.z-dn.net/?f=V_1%20%3D%203%20%2A%20V_2)
![V_1 = 3 V_2](https://tex.z-dn.net/?f=V_1%20%3D%203%20V_2)
<em>Hence, the amount of sand used in building the prism is three times the amount of sand used in building the pyramid</em>
Answer:450
Step-by-step explanation:
first subctract then add